Интелектуальная подсистема управления производством пивного солода - Мацебула, Дмитрий Валерьевич; Эльперин, Игорь Владимирович (My University, 2015)
This article is about the possibility of improving the control system of brewing malt production. The existing approaches and methods of production management malt are shown. The relation between raw materials, semi-finished and finished products qualitative measures are shown. The technique and intelligent control system based on neural networks and decision support systems structure is developed. Эта статья повествует о возможности совершенствования системы управления производством пивоваренного солода. Показаны существующие подходы и методы управления производством солода. Предоставлены качественные показатели соотношения между сырьем, полуфабрикатами и готовой продукцией. Разработаны техника и интеллектуальная система управления на основе нейронных сетей и решений структуры систем поддержки.
Keywords: malt production; intelligent subsystem; производство солода; интеллектуальные подсистемы; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка